Eksplorasi Faktor Internal dan Eksternal dalam Implementasi Dynamic Managerial Capabilities pada PT. Bixbox Teknologi Perkasa - Puspadi, Mayang Putri (Riviera Publishing, 2025)
This study aims to explore internal and external factors influencing the implementation of Dynamic Managerial Capabilities (DMC) at PT. Bixbox Teknologi Perkasa, a technology-based startup. DMC refers to the ability of managers to sense opportunities, seize them strategically, and reconfigure organizational resources in response to environmental dynamics. This qualitative research adopts a single case study approach, using in-depth interviews with key informants in managerial roles. The theoretical framework integrates the Dynamic Managerial Capabilities Framework (Heubeck, 2023a), the Entrepreneurial Learning Framework (Lecler & Kinghorn, 2014), and Emotional Intelligence Theory (Goleman, 1995). Initial findings reveal that entrepreneurial experience, emotional intelligence, and organizational culture serve as critical internal factors shaping managerial cognition and decision-making. Externally, technological disruption and market pressures act as driving forces for strategic adaptation through DMC processes. This study contributes to the theoretical understanding of micro-level enablers in developing dynamic capabilities within the context of digital startups.